Mucous Membrane Pemphigoid: A Frustrating Disabling Disease in A 15-year-old Male - Akhyar, Gardenia; Izrul, Irdawaty; Nagara, Adianto Jaya (Newinera Publisher, 2024)
Mucous membrane pemphigoid (MMP) is a rare chronic autoimmune subepithelial blistering disease characterized by erosive lesions of mucous membranes and skin that typically results in scarring of at least some sites of involvement. A progressive disorder that may result in serious complications including blindness, loss of the airway, and esophageal stricture formation. Most patient experience reduced quality of life specifically with ocular symblepharon and laryngeal destruction. Case: We present a case of a 15-year-old male patient with 1 month-history of multiple tense bullae, difficulty to open the eyes, and hoarseness due to scar lesion in mucous membrane. The patient was reported to have Dermatology Life Quality Index (DLQI) of 15 which implied he had severe disability and decreased quality of life due to his illness. Patient also had symblepharone release operation done by ophthalmologist. A laryngeal reconstruction plan was also carried out by ENT doctor, but the patient couldn’t continue the treatment because of economic problem. Scarring of MMP is a significant complication in many cases. Mucous membrane pemphigoid could cause a lot of disability to the patient and decreased quality of life. Symblepharone release operation was done and laryngeal reconstruction plan was also carried out. Surgical intervention may not curable; however, it may be necessary for restoring function and improving quality of life.